Strengthening Digital Governance for Sustainable Eco-Friendly TUS Mart Website Sevice Through the Integration of IPA, PGCV, and Webqual - Nurlaela, Norma Septin; Zunaidi, Rizqa Amelia; Chandra, Huki (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2026)
The advancement of information technology has simplified various tasks, mainly through easier mobile internet access, driven by the rise of social media platforms. Social media serves as both a virtual interaction tool and a promotional medium, including for online shopping applications, which have contributed to the growth of e-commerce in Indonesia. At Telkom University Surabaya, hydroponic and aquaponic activities have started harvesting, requiring a platform to market these products. TUS MART, an online shopping platform developed by Telkom University Surabaya, facilitates consumer access to shop anytime and anywhere. In its prototype stage, TUS MART's usability is being tested using the WebQual Concept. TUS Mart supports environmentally sustainable practices by facilitating the distribution of locally grown products using hydroponic and aquaponic farming methods. Through this approach, TUS Mart helps reduce the carbon footprint of the supply chain and promotes the consumption of healthier, more sustainable products. The study employs the Importance Performance Analysis (IPA) and Potential Gain in Customer Value (PGCV) methods to assess and prioritize improvements. The PGCV index identifies key attributes for service quality enhancement. Prioritized improvements include variable E4 in the Entertainment dimension (minimizing excessive ads), E3 in the Entertainment dimension (attractive text forms), W7 in the Web Appearance dimension (engaging content composition), and W6 in the Web Appearance dimension (attention-grabbing colors). These findings provide actionable insights for optimizing TUS MART's service quality.